The Running Wheel Enhances Food Anticipatory Activity: An Exploratory Study - Flôres, Danilo E. F. L.; Bettilyon, Crystal N.; Jia, Lori; Yamazaki, Shin (Frontiers in Behavioral Neuroscience, 2016)
Rodents anticipate rewarding stimuli such as daily meals, mates, and stimulant drugs. When a single meal is provided daily at a fixed time of day, an increase in activity, known as food anticipatory activity (FAA), occurs several hours before feeding time. The factors affecting the expression of FAA have not been well-studied. Understanding these factors may provide clues to the undiscovered anatomical substrates of food entrainment. In this study we determined whether wheel-running activity, which is also rewarding to rodents, modulated the robustness of FAA. We found that access to a freely rotating wheel enhanced the robustness of FAA. This enhancement was lost when the wheel was removed. In addition, while prior exposure to a running wheel alone did not enhance FAA, the presence of a locked wheel did enhance FAA as long as mice had previously run in the wheel. Together, these data suggest that food anticipatory activity, like wheel-running activity, is influenced by reward signaling.